Effectiveness Of An English Language Skills Development Program Based On Time Management For The Community: A Case Study Of The Cijaya Purwakarta Village - Devi Nopianti; Andika Maulana Somantri (Riviera Publishing, 2024)
This research paper presents a case study on the effectiveness of an English language skills development program based on time management for the Cijaya Purwakarta village community in Indonesia. The study aimed to assess the impact of the program on participants' English proficiency, as well as to explore their perceptions of the program's strengths, challenges, and overall effectiveness. The program was implemented over a 24-week period and incorporated various time management strategies and regular practice opportunities for the participants. The participants attended once in a week sessions that focused on developing their English language skills, including vocabulary, grammar, speaking, and listening. The study utilized a mixed-methods approach, combining quantitative and qualitative data collection and analysis. Standardized tests were used to measure the participants' English language skills before and after the program, while qualitative data was collected through focus group discussions and individual interviews to gauge their perceptions of the program's effectiveness.